Effect of shielding gas composition and welding speed on autogenous welds of unalloyed tungsten plates. (December 2019) - Marinelli, G.; Martina, F.; Ganguly, S.; Williams, S.
Abstract: Tungsten usually exhibits poor weldability and marked brittleness at room temperature. This causes tungsten welds to be affected by the evolution of cracks along the weld bead, which can be eliminated by using a pre-heating step to reduce thermal straining. In this study, based on the tungsten inert gas welding process, a working envelope, focussed on varying welding speed and five different shielding gas mixtures of argon and helium, has been defined with the view of producing crack-free autogenous welds. The bead appearance and the microstructure of the different welds were correlated to the welding parameters, whose main effects have been analysed. Welding defects such as humping occurred when using gas mixtures with relatively low content of helium, and when using relatively high welding speeds. Crack-free autogenous welds have been produced without pre-heating when using a high content of helium and relatively low welding speeds. Thus, this study has demonstrated that a helium-rich shielding gas is required for welding thick tungsten plates. Moreover, the low thermal shock induced by the process, coupled with the purity of the tungsten plates used, strongly contributed to avoid the occurrence of any crack. Graphical abstract: Unlabelled Image Highlights: Helium-rich gas mixtures are required to obtain controlled melting of tungsten. Process heat flux and defects occurrence depend on the composition of the gas used. Crack-free tungsten welds can be produced using Tungsten Inert Gas welding. The process-induced thermal shock can be reduced by decreasing the welding speed.